Superior wide-temperature lithium storage in a porous cobalt vanadate - Chen, Haoliang (2020)
Lithium ion batteries (LIBs) that can be operated under extended temperature range hold significant application potentials. Here in this work, we successfully synthesized Co2V2O7 electrode with rich porosity from a facile hydrothermal and combustion process. When applied as anode for LIBs, the electrode displayed excellent stability and rate performance in a wide range of temperatures. Remarkably, a stable capacity of 206 mAh·g−1 was retained after cycling at a high current density of 10 A·g−1 for 6,000 cycles at room temperature (25 °C). And even when tested under extreme conditions, i.e., −20 and 60 °C, the battery still maintained its remarkable stability and rate capability. For example, at −20 °C, a capacity of 633 mAh·g−1 was retained after 50 cycles at 0.1 Ag−1; and even after cycling at 60 °C at 10 A·g−1 for 1,000 cycles, a reversible capacity of 885 mAh·g−1 can be achieved. We believe the development of such electrode material will facilitate progress of the next-generation LIBs with wide operating windows. [Figure not available: see fulltext.].